The relative safety of morning and afternoon exercise in patients with coronary artery disease - Santolin, Barbara E. (My University, 1994)
Sixteen males (mean age = 62.1 yrs) with documented coronary artery disease performed a 30-minute bout of exercise in the morning (6:OO - 8:00 a.m.) and in the afternoon (4:00 - 6:00 p.m.). Each session was conducted on a motorized treadmill at an identical speed and grade.
Keywords: Circadian rhythms; Coronary heart disease - Exercise therapy; Coronary heart disease - Patients - Rehabilitation